The Dimensions of Organizational Character and Its Impacts on Organizational Performance in Chinese Context - Yu, Dengke; Xiao, Huan; Bo, Qiushi (Frontiers in Psychology, 2018)
As an organic entity, organization is similar to human, having unique organizational character which constitutes a source of competitive differentiation. This study aims to explore the dimensions of organizational character and measure its impacts on organizational performance in Chinese context. Since several previous studies have developed the definition and constitutions of organizational character in the context of developed countries such as America and England, this indigenous study provides new evidence from the perspective of emerging economy. A research model using qualitative analysis method is proposed to define the dimensions of organizational character. The connection between organizational character and organizational performance is empirically tested by a multi-ordered logit regression analysis with a survey of 205 observations in Chinese enterprises. The dimension of organizational character is finally extracted and summarized as six aspects including enterprise, conscientiousness, innovation, agreeableness, democracy and Boy Scout. The results of empirical analysis show that the formation and cultivation of organizational character would directly improve organizations’ business performance as well as their growth potential. It is worth noting that a special part of organizational character which may depend more on national culture or institutional background than organizational individuals also makes impacts on organizational performance. The findings can provide practical implications for Chinese companies and multi-national companies that do or plan to do business in China. Entrepreneurs are suggested to make effective decisions on the cultivation of organizational character, since different types and specific levels of organizational character may have significantly different effects on organizational performance. This paper explores a novel theory to explain the antecedents of organizational performance, and would inspire scholars to expand the sources of organizational competitive advantage in the future.